2011
DOI: 10.1111/j.1365-2966.2011.18980.x
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén wave amplification and self-containment of cosmic rays escaping from a supernova remnant

Abstract: We study the escape of cosmic ray (CR) protons accelerated in a supernova remnant (SNR) by numerically solving a diffusion–convection equation for regions from the vicinity of the shock front to those far away from the front. We consider the amplifications of Alfvén waves generated by the escaping CR particles and their effects on CR escape into the interstellar medium (ISM). We find that the amplification of the waves significantly delays the escape of the particles even in regions far away from the shock fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…Theoretically, this phenomenon is also studied by Monte Carlo simulation, in which the CR streaming instability can generate Alfvén waves. The waves strongly scatter the particles and make the particle diffusion in the ISM around the SNR remarkably slow, and the diffusion coefficient is therefore strongly suppressed (Fujita, Ohira & Takahara 2010; Fujita et al 2011). This kind of suppression is significant if the ambient ISM is well ionized for the CRs around the SNRs, because the neutral damping of Alfvén waves is not effective.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Theoretically, this phenomenon is also studied by Monte Carlo simulation, in which the CR streaming instability can generate Alfvén waves. The waves strongly scatter the particles and make the particle diffusion in the ISM around the SNR remarkably slow, and the diffusion coefficient is therefore strongly suppressed (Fujita, Ohira & Takahara 2010; Fujita et al 2011). This kind of suppression is significant if the ambient ISM is well ionized for the CRs around the SNRs, because the neutral damping of Alfvén waves is not effective.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…They concluded that only a rather small diffusion coefficient, ∼100 times lower A56, page 6 of 8 than the Galactic one, and a short distance from the SNR, of about 40 pc, could reconcile the detection of TeV emission, the GeV upper limits at the location of the HESS source, and the cloud mass derived by Paron & Giacani (2010). Nevertheless, given the small projected distance of ∼5 pc (at a distance of 3.6 kpc) between the cloud and the SNR, plus the fact that close to SNR shocks particle propagation may be significantly slowed down (Fujita et al 2011;Malkov et al 2013), the connection between the TeV emission and the SNR cannot be discarded. In fact, new calculations modelling the interaction between the SNR cosmic rays and the cloud, using the distance of 3.6 kpc, relax the conditions on the diffusion coefficient and cloud mass, making this possibility more likely than previously thought (see discussion in Zhu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(56-57) but different assumptions are made regarding geometry of particle escape from the source (see (i) above), the character and strength of wave damping Γ (iv), and the role of quasilinear wave saturation (iii). Fujita et al (2011) and Yan et al (2012) utilize the isotropic escape models (in this case ∂/∂z should be replaced by ∂/∂r, etc.) while Ptuskin et al (2008) and Malkov et al (2012a) assume that particles propagate predominantly along the local large-scale field.…”
Section: Self-confinement Of Crs Near Their Acceleration Sitesmentioning
confidence: 99%